Effect of PCBM on the photodegradation kinetics of polymers for organic photovoltaics - Distler, Andreas; Kutka, Peter; Sauermann, Tobias; Egelhaaf, Hans-Joachim; Guldi, Dirk Michael; Di Nuzzo, Daniele; Meskers, Stefan C. J.; Janssen, Rene A. J. (Chemistry of Materials, 2012)
The photo-oxidation behavior of three different polymers-namely, poly(3-hexylthiophene) (P3HT), poly[2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta[2, 1-b;3,4-b′]dithiophene)-alt-4,7-(2,1,3-benzothiadiazole)] (C-PCPDTBT), and poly[2,6-(4,4-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]silole)-alt- 4,7-(2,1,3-benzothiadiazole)] (Si-PCPDTBT)-is investigated in neat polymer films and in blends with [6,6]-phenyl-C-butyric acid methyl ester (PCBM) for different polymer:PCBM ratios. PCBM is shown to have both stabilizing and destabilizing effects, the extent of which is dependent on the type of polymer with which it is blended. Screening of the polymer from incident light by PCBM turns out to play an only minor role in the stabilization of P3HT. Quenching of the polymer excited states is also not a significant stabilization mechanism, as demonstrated by the comparison of the reduction of photo-oxidation rates to the extent of photoluminescence quenching by PCBM and 2,7-dinitrofluorenone (DNF). Photoinduced absorption spectroscopy reveals that the enhanced degradation of C-PCPDTBT in blend films with PCBM correlates with the population of the polymer triplet state via the polymer:PCBM charge-transfer state. © 2012 American Chemical Society.

The Effect of PCBM Dimerization on the Performance of Bulk Heterojunction Solar Cells - Distler, Andreas; Sauermann, Tobias; Egelhaaf, Hans-Joachim; Rodman, Sheila; Waller, Dave; Cheon, Kap-Soo; Lee, Mike; Guldi, Dirk Michael (Advanced Energy Materials, 2013)
Increasing the lifetime of polymer based organic solar cells is still a major challenge. Here, the photostability of bulk heterojunction solar cells based on the polymer poly[4,4'-bis(2-ethylhexyl)dithieno[3,2-b:2',3'-d]silole)-2,6-diyl-alt-[2,5-bis(3-tetradecylthiophen-2-yl)thiazole[5,4-d]thiazole)-1,8-diyl] (PDTSTzTz) and the fullerene [6,6]-phenyl-C-butyric acid methyl ester (PCBM) under inert atmosphere is investigated. Correlation of electrical measurements on complete devices and UV-vis absorption measurements as well as high-performance liquid chromatography (HPLC) analysis on the active materials reveals that photodimerization of PCBM is responsible for the observed degradation. Simulation of the electrical device parameters shows that this dimerization results in a significant reduction of the charge carrier mobility. Both the dimerization and the associated device performance loss turn out to be reversible upon annealing. BisPCBM, the bis-substituted analog of PCBM, is shown to be resistant towards light exposure, which in turn enables the manufacture of photostable PDTSTzTz:bisPCBM solar cells. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinhei